Transforming rural China : how local institutions shape property rights in China - Chen, Chih-Jou Jay, 1966- (London ; New York : RoutledgeCurzon, 2004)
It is often assumed that privatization leads to profit, and that well-delineated property rights and a strong private sector will help boost economy. This book investigates the property rights in Chinese enterprises in the reform era.
Explaining property rights transformations -- The Yangtze delta in the reform era -- The Yangtze delta in the post-reform era -- Shuang village : the case study -- Southern Fujian under economic reforms -- Hancun village : the case study -- Conclusion: local institutions and the future of China.
Includes bibliographical references (pages 188-207) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Land use, Rural -- China; Rural development -- China; Right of property -- China; China -- Economic policy -- 2000-; Utilisation agricole du sol -- Chine; Développement rural -- Chine; Droit de propriété -- Chine; Chine -- Politique économique -- 2000-; BUSINESS & ECONOMICS -- Real Estate -- General; Economic policy; Land use, Rural; Right of property; Rural development; China; Plattelandsontwikkeling; Eigendomsrecht; Since 2000